Association of the interleukin (IL)-16 gene polymorphisms with Graves' disease - Gu, Xue-Jiang (Clinical immunology (Orlando, Fla.), 2008)
Interleukin (IL)-16 was one of the cytokines with the function of T helper cell recruitment, whose expression in the thyrocyte and orbital fibroblast of Graves' disease (GD) patients was increased. Recently association of IL-16 gene polymorphisms with autoimmune diseases had been reported. However, there was little known about the impact of IL-16 gene polymorphisms on GD. In this study, we performed a case-control association study of three tagSNPs (rs4778889-rs1131445-rs4778641) within the IL-16 gene on 258 patients with GD and 208 healthy subjects in the Chinese population. Our data showed that common IL-16 variants were associated with GD (P=0.013-0.0186) and Graves' disease associated ophthalmopathy (GO) (P=0.0033-0.041). A novel protective haplotype containing the three tagSNPs (C-T-C) was observed in association with GO (P=0.013). In conclusion, IL-16 gene was significantly associated with susceptibility to Graves' disease and Graves' disease associated ophthalmopathy in the Chinese population